Out of the box - Westing, Jemma (DK Publishing, 2017)
"Recycle household cardboard into incredible art projects that you can wear, share, and play with. Learn how to build and decorate more than 25 amazing creations, including costumes and castles, gifts and games, puppets and pirate ships"--